An interpretable machine learning prognostic system for risk stratification in oropharyngeal cancer - Alabi Rasheed Omobolaji; Almangush Alhadi; Elmusrati Mohammed; Leivo Ilmo; Mäkitie Antti A. (ELSEVIER IRELAND LTD, 2022)
Background: The optimal management of oropharyngeal squamous cell carcinoma (OPSCC) includes both surgical and non-surgical, that is, (chemo)radiotherapy treatment options and their combinations. These approaches carry a risk of specific treatment-related side effects. HPV-positive OPSCC has been reported to be more sensitive to (chemo)radiotherapy-based treatment modalities.
Objectives: This study aims to demonstrate how machine learning can aid in classifying OPSCC patients into risk groups (low-chance or high-chance) for overall survival. We examined the input variables using permutation feature importance. Furthermore, we provided explanations and interpretations using the Local Interpretable Model Agnostic Explanations (LIME) and SHapley Additive Explanation (SHAP) frameworks.
Methods: The machine learning model for 3164 OPSCC patients was built using data obtained from the Surveillance, Epidemiology, and End Results (SEER) program database. A total of five variants of tree-based machine learning algorithms (voting ensemble, light GBM, XGBoost, Random Forest, and Extreme Random Trees) were used to divide the patients into risk groups. The developed model with the best predictive performance was temporally validated with a different cohort.
Results: The voting ensemble machine learning algorithm showed an accuracy of 88.3%, Mathews’ correlation coefficient of 0.72, and weighted area under curve of 0.93, when temporally validated. Human papillomavirus (HPV) status, age of the patients, T stage, marital status, N stage, and the treatment modality (surgery with postoperative radiotherapy) were found to have the most significant effects on the ability of the machine learning model to predict overall survival. Similarly, for the individual patients with SHAP framework, HPV status, gender, and treatment modality (surgery with postoperative radiotherapy) were the input features that improved the model’s prediction.
Conclusion: The proposed stratification of OPSCC patients into risk groups by machine learning techniques can provide accurate predictions and thus aid clinicians in administering early and personalized interventions. Clinicians could utilize the predicted risk with the explanations offered by the SHAP and LIME frameworks to understand previously undetected relationships between prognostic variables to make informed clinical decisions and effective interventions.